2017
DOI: 10.1002/elan.201700120
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cerium Tungstate Nanosheets Modified Electrode for the Effective Electrochemical Detection of Carcinogenic Nitrite Ions

Abstract: In this present scenario, for the first time, we propose a facile and simple wet chemical approach for the fabrication of two‐dimensional (2D) cerium tungstate (CeW2O9;CeW) nanosheets and evaluated as an electrochemical sensor for the detection of nitrite ions. The successful formation of CeW2O9 nanosheets was confirmed by various physicochemical techniques such as X‐ray diffraction, Fourier transform infrared spectroscopy, Raman, Scanning electron microscope, Transmission electron microscope and Energy disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…The linear regression equation for ν 1/2 vs I pa plot can be written as I pa (μA) = 142.76 ν 1/2 + 901.08 with a correlation coefficient of 0.982. Our study confirmed that the NO oxidation at the WO 3 -90 electrode is diffusion-controlled . The repeatability of the Au-WO 3 sensing electrode was tested with 50 cycles of CV scan with 100 mV/s scan rate, and a very small change in oxidation current has been observed (Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The linear regression equation for ν 1/2 vs I pa plot can be written as I pa (μA) = 142.76 ν 1/2 + 901.08 with a correlation coefficient of 0.982. Our study confirmed that the NO oxidation at the WO 3 -90 electrode is diffusion-controlled . The repeatability of the Au-WO 3 sensing electrode was tested with 50 cycles of CV scan with 100 mV/s scan rate, and a very small change in oxidation current has been observed (Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The choice of Bi 2 WO 6 and NiWO 4 is influenced by the fact that the use of small metals such as Bi in MWO x results in a narrower band gap, which has been found to be beneficial in electrocatalysis of reactions such as oxygen reduction reaction [15, 17, 18]. Metal tungstate nanoparticles have previously been reported for the detection of analytes including nitrite [2, 6, 19]. This work explores the covalent conjugation of bismuth‐tungsten (Bi 2 WO 6 ) and nickel‐tungsten (NiWO 4 ) nanoparticles (NPs) to a cobalt phthalocyanine molecule (CoPc).…”
Section: Introductionmentioning
confidence: 99%
“…From the other hand, it plays a role in reducing the effect of interferents. Recently, hybrid nanostructured materials have been widely employed in sensing applications thanks to their high surface area, reasonable biocompatibility, catalytic activity, chemical stability, and high electrical conductivity [ 25 , 26 , 27 , 28 , 29 ]. Carbon nanotubes (CNTs) and compared to the other carbon electrodes are found to be advantageous in terms of sensitivity, selectivity, response time, reusability, and the resistance to surface fouling [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%